Missing May - Rylant, Cynthia (New York : Dell, 1993)
After the death of the beloved aunt who has raised her, twelve-year-old Summer and her uncle Ob leave their West Virginia trailer in search of the strength to go on living.
"A Richard Jackson book"--Half t.p.
BL, BCCB, HB, K, PW, SLJ, VOYA
5.8
005-009
980
Accelerated Reader AR
Keywords: Newbery award; Death -- Fiction; Grief -- Fiction; Joy -- Fiction; Aunts -- Fiction; Death -- Fiction; Grief -- Fiction; Aunts -- Fiction; West Virginia -- Fiction; West Virginia -- Fiction